NEW NORMAL : DALAM PESAN IKLAN TV KOMERSIAL TRAVELOKA - Hermanto, Agus; Adawiyah, Sa’diyah El; Effendi, Cecep; Patrianti, Tria (Jurnal Bahasa Rupa, 2021)
This article aims to know the display and narrative new normal in the Traveloka Commercial TV ad message regarding a new way of life in relation to the Covid 19 pandemic. Using a qualitative approach with narrative analysis; how do communicators tell stories, this research was conducted. Through observation of Traveloka #JalanBersamaAnda TV advertising material and literature study, data collection techniques were carried out. One by one, analyzing each frame and duration of advertisements and selecting and classifying them according to the research focus for data presentation. The finding in this article is that Traveloka commercial TV commercials carry #JalanBersama as the big idea foundation. Presenting ten visual stories of environmental atmosphere and some unusual daily activities of people in early 2020 related to the COVID-19 pandemic.